Antigone’s resistant body: Hegel, Weil, Irigaray - Carofalo, Viola (B@belonline, 2022)
Throughout her career, Luce Irigaray has had a tumultuous but enduring relationship with Hegel’s philosophy, evidence of which is present in all her work. Irigaray sees the critical comparison with Hegel as an imperative tied to the necessity of liberating culture from male dominance; this reinterpretation is condensed in the figure of the Sophoclean heroine Antigone. Antigone’s body – buried alive – represents not only the price of love, but also the irruption, on the public scene, of a Subject that is, normally, erased. Antigone represents the subordinate, the last, the forgotten; Irigaray and Weil, another central author in the reinterpretation path proposed here, try to give space and voice to these cancelled existences.